Pemanfaatan Smartphone Sebagai Media BK dalam Mengatasi Masalah Belajar Siswa di SMP Islam Al-Ulum Terpadu Medan - Vivi Nabila (Universitas Islam Negeri Sumatera Utara Medan, 2021)
This study aims to describe the use of smartphones as a counseling medium in overcoming student learning problems at the Al-Ulum Terpadu Islamic Junior High School Medan. This study uses qualitative analysis and uses subjects called informants, namely BK teachers, subject teachers, and five class VII students who are determined from the results of interviews with BK teachers and subject teachers with the aim of considering that the informants understand, know and feel directly to the problem at hand. The results of this study indicate that the use of smartphones as a counseling medium in overcoming student learning problems that has been carried out by BK teachers to students at the Al-Ulum Terpadu Islamic Middle School in Medan systematically and sustainably provides positive and effective changes in generating students’ willingness to learn who initially felt lazy,bored and bored in learning, even easily underestimate learning. Now has a high willingness to learn by using various applications such as WhatsApp, Zoom and Google Classroom which are packaged as attractively as possible. This is evidenced by the implementation and results achieved so far in generating students’ willingness to learn. With students’ willingness to learn, it is expected that students can digest and accept learning well.